IMPLEMENTASI KEPEMIMPINAN STRATEGIS DANPASMAR GUNA KESIAPAN OPERASI KORPS MARINIR YANG ADAPTIF - Argo Setiyono; Cahyadi Amperawan (Faculty of Social and Political Sciences Universitas Prof Dr Hazairin, SH, 2024)
This research was conducted against the backdrop of increasingly complex national defense challenges in the VUCA (Volatile, Uncertain, Complex, and Ambiguous) era. Threats to national sovereignty, especially hybrid threats, require the Marine Corps, specifically the Marine Forces (Pasmar), to possess a high degree of adaptability. One key factor in improving Pasmar's operational readiness is strategic leadership. Therefore, this study aims to analyze the effectiveness of the implementation of strategic leadership by the Pasmar Commander (Danpasmar) in enhancing the unit's operational readiness. This study uses a qualitative method. The analysis method used is the Miles and Huberman analysis, which focuses on leadership factors and operational readiness identified in the Pasmar context. The results of the study indicate that the strategic leadership carried out by the Pasmar Commander has an important role in building adaptive operational readiness. The strategies implemented, such as updating Defense Equipment, developing soldier professionalism, and strengthening collaboration between units, significantly improve Pasmar's ability to respond to emerging threats. It can be concluded that the strategic leadership of Danpasmar 1 has succeeded in improving the operational readiness of the Marine Corps by managing five main components: strategic direction, resource management, organizational culture, ethics, and control. Danpasmar 1 formulates an adaptive long-term strategy, utilizes technology, and manages resources efficiently. Good relations with external parties and regular evaluations also support high operational readiness. Danpasmar 1's strategy involves dynamic adaptation, effective resource management, clear communication, continuous coaching, and strategy adjustments. Danpasmar 1's strategic leadership plays a crucial role in improving Pasmar 1's operational readiness to face increasingly complex defense challenges in the future.